2004
DOI: 10.1637/7104
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Nicotinamide Adenine Dinucleotide–Independent Haemophilus paragallinarum in México

Abstract: Two isolates of Haemophilus paragallinarum were obtained from a layer chicken in Mexico. The isolates were confirmed as H. paragallinarum by polymerase chain reaction and conventional biochemical identification. The isolates were nicotinamide adenine dinucleotide (NAD) independent-growing on blood agar without the need of a nurse colony as well as on a complex medium that lacked both NAD and chicken serum. Both isolates were pathogenic, causing the typical clinical signs of infectious coryza in susceptible chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…Recently, biovar 2 isolates of [Haemophilus] paragallinarum have been identified in Mexico (García et al, 2004). While these biovar 2 isolates were not available for the current study, the Mexican isolates have been shown to be positive in the [Haemophilus] paragallinarum-specific PCR and have been allocated to existing Page serovars (García et al, 2004). This is strong evidence that these new Mexican biovar 2 isolates of [Haemophilus] paragallinarum are also typical of the species Avibacterium paragallinarum.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Recently, biovar 2 isolates of [Haemophilus] paragallinarum have been identified in Mexico (García et al, 2004). While these biovar 2 isolates were not available for the current study, the Mexican isolates have been shown to be positive in the [Haemophilus] paragallinarum-specific PCR and have been allocated to existing Page serovars (García et al, 2004). This is strong evidence that these new Mexican biovar 2 isolates of [Haemophilus] paragallinarum are also typical of the species Avibacterium paragallinarum.…”
mentioning
confidence: 69%
“…Characters are scored as: +, 90 % or more of strains positive within 1-2 days; (+), 90 % or more of strains positive within 3-14 days; 2, less than 10 % of strains positive within 14 days; d, 11-89 % of strains positive; W, weakly positive. Recently, biovar 2 isolates of [Haemophilus] paragallinarum have been identified in Mexico (García et al, 2004). While these biovar 2 isolates were not available for the current study, the Mexican isolates have been shown to be positive in the [Haemophilus] paragallinarum-specific PCR and have been allocated to existing Page serovars (García et al, 2004).…”
mentioning
confidence: 99%
“…Previous reports in 1992 (16,22) refused to designate NAD-I isolates as A. paragallinarum because of the NAD independence, despite the fact that clinical signs and culture characteristics corresponded to A. paragallinarum. Later, there were other reports of IC caused by NAD-I A. paragallinarum from South Africa (10,21) and Mexico (14); the NAD-independent species of Haemophilus (15,27) contributed to the acknowledgment that both NAD-D and NAD-I should be accepted as A. paragallinarum (5).…”
Section: Resultsmentioning
confidence: 99%
“…However, reports from South Africa (6,10,16,21) and Mexico (14), have demonstrated the isolation of NAD-independent (NAD-I) bacteria, supporting the idea that this requirement is not an obligatory characteristic for identifying the bacterium; consequently, both NAD-dependent (NAD-D) and NAD-I isolates are now recognized as A. paragallinarum (5).…”
mentioning
confidence: 90%
“…While this organism has traditionally been regarded as requiring nicotinamide adenine dinucleotide (V factor), but not haemin (X factor), for growth in vitro (Blackall & Matsumoto, 2003), nicotinamide adenine dinucleotide-independent forms have been recognized in both South Africa and México (Horner et al, 1992;Mouahid et al, 1992;Garcia et al, 2004). Two serotyping schemes exist*the Page scheme, which recognizes serovars A, B and C (Page, 1962); and the Kume scheme, which recognizes serogroups A, B and C with four serovars each within serogroups A and C (Blackall et al, 1990b).…”
Section: Introductionmentioning
confidence: 99%